Dekonstruksi Dalam Cerpen Saksi Mata Karya Agus Noor - Rahmin Meilani Putri (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This research reveals the existence of a number of binary oppositions and dismantling of the order contained in the short story Saksi Mata by Agus Noor. Saksi Mata short stories were chosen because they reveal something unusual and even inversely proportional to what we find in people's lives factually. The analysis in the short story Saksi Mata was carried out using a deconstruction approach. This research is a qualitative study and is presented descriptively. The primary data in this study is in the form of a short story with the title Saksi Mata and secondary data in the form of a number of severences that support the arrangement and answer of problems in this study. Data obtained by conducting in-depth readings of primary data and recording identified narratives that can answer research problems. The results of the data analysis carried out were obtained by a number of binary oppositions, namely hope and reality, honor and humiliation, testimony and blindness, eyewitnesses and defendants, stupid and clever, madness and power, as well as losers and heroes. The demolition of the order was carried out by presenting a blind dog figure as an eyewitness in a murder case at a trial.